2002
DOI: 10.1063/1.1526916
|View full text |Cite
|
Sign up to set email alerts
|

Tbit/inch 2 ferroelectric data storage based on scanning nonlinear dielectric microscopy

Abstract: Nanosized inverted domain dots in ferroelectric materials have potential applications in ultrahigh-density rewritable data storage systems. Here, a data storage system based on scanning nonlinear dielectric microscopy and thin films of ferroelectric single-crystal lithium tantalite is presented. Through domain engineering, nanosized inverted domain dots have been successfully formed at a data density of 1.50 Tbit/in.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
107
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(108 citation statements)
references
References 9 publications
1
107
0
Order By: Relevance
“…15,[19][20][21][22][23][24][25] Studies have shown that metallic nanoparticle deposition from an aqueous solution onto þZ surfaces of LiNbO 3 domain patterns can be achieved. [23][24][25] The nanopatterned features created using Ag nanoparticles possessed a uniform distribution with a size variation between 2 and 10 nm in both diameter and height.…”
mentioning
confidence: 99%
“…15,[19][20][21][22][23][24][25] Studies have shown that metallic nanoparticle deposition from an aqueous solution onto þZ surfaces of LiNbO 3 domain patterns can be achieved. [23][24][25] The nanopatterned features created using Ag nanoparticles possessed a uniform distribution with a size variation between 2 and 10 nm in both diameter and height.…”
mentioning
confidence: 99%
“…Ferroelectric domain engineering by scanning probe microscopy (SPM) is a rapidly evolving technology that can be used for the development of high-density data storage, nonlinear optical devices and ferroelectric lithography. [1][2][3][4][5][6][7] Nanoscale domain patterns may also enable new approaches to fabrication of molecular structures for biological and chemical sensors. The key issues in SPM domain engineering are writing resolution and domain stability which depend both on the domain growth kinetics and on the domain size in the thermodynamically equilibrium state.…”
mentioning
confidence: 99%
“…Domain engineering in ferroelectric crystals is of increasing importance for quasi-phasematched second-harmonic generation [1], nonlinear photonic crystals [2], and ultra-high density data storage devices [3]. Among the techniques utilized for the visualization of ferroelectric domains [4] piezoresponse (or piezoelectric) force microscopy has become an established standard tool because of its non-destructive imaging capability with high lateral resolution [5,6].…”
mentioning
confidence: 99%